Comparison of survival between radiation therapy and trans-oral laser microsurgery for early glottic cancer patients; a retrospective cohort study. Issue 1 (December 2016) - De Santis, R.; Poon, I.; Lee, J.; Karam, I.; Enepekides, D.; Higgins, K.
Abstract Background The literature reports various treatment methodologies, such as trans-oral laser microsurgery, radiation therapy, total/partial laryngectomies, and concurrent radiation chemotherapy for patients with early larynx cancer. However, at the forefront of early glottis treatment is trans-oral laser microsurgery and radiation therapy, likely due to better functional and survival outcomes. Here we conduct the largest Canadian head-to-head comparison of consecutive patients treated with either radiation therapy or trans-oral laser microsurgery. Additionally, we compare these two treatments and their 5-year survival rates post treatment to add to the existing literature. Methods Charts of patients who were diagnosed with early glottic cancer between 2006 and 2013 were reviewed. Seventy-five patients were identified, and split into 2 groups based on their primary treatment, trans-oral laser microsurgery and radiation therapy. Kaplan–Meier survival curves, life-tables, and the log-rank statistic were reported to determine if there was a difference between the two treatment groups and their disease-specific survival, disease-free survival, and total laryngectomy-free survival. Additionally, each different survival analysis was stratified by potential confounding variables, to help conclude which treatment is more efficacious in this population. Results The 5-year disease-specific survival rate is 93.3 % σ = 0.063 and 90.8 % σ = 0.056 for patients treated with trans-oral laser microsurgery and radiation therapy, respectively (χ 2 < 0.001, p = 0.983). The disease free survival rate is 60.0 % (σ =0.121) for patients treated with trans-oral laser microsurgery, and 67.2 % (σ = 0.074) for those who received RT (χ 2 = 0.19, p = 0.663). Additionally, the total laryngectomy-free survival rate is 84.1 % (σ = 0.1) and 79.1 % (σ = 0.072) for patients' early glottic cancer treated by trans-oral laser microsurgery and radiation therapy, respectively (χ 2 = 0.235, p = 0.628). Chi-square analysis of age-group versus treatment group (χ 2 = 6.455, p = 0.04) and T-stage versus treatment group (χ 2 = 11.3, p = 0.001) revealed a statistically significant relationship, suggesting survival analysis should be stratified by these variables. However, after stratification, there was no statistically significant difference between the trans-oral laser microsurgery and radiation therapy groups in any of the survival analyses. Conclusion No difference was demonstrated in the 5-year disease-specific survival, disease-free survival, and total laryngectomy-free survival, between the RT and TLM treatment groups. Additionally, both groups showed similar 5-year survival after stratifying by confounding variables.